2006
DOI: 10.3928/1081-597x-20061001-05
|View full text |Cite
|
Sign up to set email alerts
|

Topographic- and Wavefront-guided Customized Ablations With the NIDEK-EC5000CXII in LASIK for Myopia

Abstract: PURPOSE: To assess refractive outcomes, changes in the total higher order root mean square (RMS) aberration, and changes in higher order wavefront aberrations after LASIK for myopia and myopic astigmatism with the NIDEK Advanced Vision Excimer Laser platform (NAVEX) using either an aspheric or topography-based or whole eye wavefront ablation algorithm. METHODS: This was a retrospective study of 1459 eyes that underwent LASIK for myopia and myopic astigmatism. The mean preoperative spherical equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…12,[17][18][19] One study 20 found that the OPDCAT algorithm induces fewer ocular HOAs than customized aspheric transition zone (CATz) ablation based on corneal topography. However, other studies 21,22 found CATz to be more predictable and to induce less aberration than OPD-CAT. There is no conclusive evidence that 1 algorithm provides better refractive outcomes.…”
Section: Resultsmentioning
confidence: 92%
“…12,[17][18][19] One study 20 found that the OPDCAT algorithm induces fewer ocular HOAs than customized aspheric transition zone (CATz) ablation based on corneal topography. However, other studies 21,22 found CATz to be more predictable and to induce less aberration than OPD-CAT. There is no conclusive evidence that 1 algorithm provides better refractive outcomes.…”
Section: Resultsmentioning
confidence: 92%
“…Our study is unique in that it differentiates the efficacy of astigmatic correction based on the location of the astigmatism on the visual axis and derives an index of success for each type. Several studies have assessed the effectiveness of correcting HOAs measured by wavefront and the secondary impact on anterior corneal astigmatism [10][11][12][13][14][15][16] ; however, to our knowledge, ours is the only study to assess the effect of treating only LOAs on the anterior cornea and the relationship between the treatment's efficacy and the origin and location of the astigmatism preoperatively. The results are equally relevant to wavefrontguided treatments.…”
Section: Discussionmentioning
confidence: 98%
“…Considerable progress has been made in recent years in developing topographicguided technology designed to treat corneal aberrations at their sourcedthe cornea 13 das well as a hybrid approach combining topographic-guided treatment with wavefront-guided treatment. [9][10][11][13][14][15][16][17][18][19] Although it is now commonly accepted that topographyguided treatment should be considered in eyes with irregular corneal astigmatism (higher-order aberrations [HOAs]), the importance of detecting the location of regular astigmatism (lower-order aberration [LOA]) preoperatively in planning routine laser-vision correction treatment is often overlooked.…”
mentioning
confidence: 99%
“…Improvements in excimer laser technology have led to reproducible and safe results. The improvements include the introduction of highly sophisticated tracking systems, 1 a decreased laser-beam spot size, 2 linking of laser platforms with topography and wavefront analyzer systems, 3 and an increased repetition rate. 4 Photorefractive keratectomy (PRK) was the first widely used refractive procedure.…”
mentioning
confidence: 99%